Impacting-freezing dynamics of a supercooled water droplet on a cold surface: Rebound and adhesion - Zhang, Xuan; Liu, Xin; Wu, Xiaomin; Min, Jingchun (International journal of heat and mass transfer, 2020)
•The impacting and freezing experiments of supercooled water droplets are conducted.•The impacting-freezing behaviors of supercooled water droplets are simulated.•The numerical model considers the supercooling effect and dynamic contact angle.•The supercooled droplet spreads and retracts slower than the room temperature one.•A morphology map of rebound and adhesion is proposed for the impacting-freezing. The impacting-freezing dynamics of a supercooled water droplet on a cold surface is studied experimentally and numerically. A numerical model that considers both the effects of the supercooling degree on the physical properties and of the dynamic contact angle on the contact line motion is established to simulate the droplet impacting-freezing behaviors using the VOF multiphase model and the Solidification/Melting phase change model. Experiments are also conducted for the impacting-freezing processes of supercooled and room temperature water droplets on a cold surface and for the impacting process of a room temperature droplet on a room temperature surface. Both the temporal droplet profile and the spreading factor calculated by the simulations agree well with the experimental observations. The maximum deviation of the maximum and stable spreading factors between experiments and simulations is 11.3%. The numerical and experimental results elucidate that the supercooled droplet spreads and retracts slower than the room temperature one in the impacting process and thus yields a smaller maximum and a larger stable spreading factor. The increases of the Weber number and supercooling degree and the decrease of the contact angle will enlarge the above differences. Additionally, three different morphologies of full rebound, partial rebound and full adhesion are identified in the impacting-freezing process of a supercooled droplet on a cold hydrophobic surface, indicating the competition between the fluid flow and heat transfer. A unified morphology map of rebound and adhesion correlating the Weber number, supercooling degree and contact angle is proposed for the impacting-freezing behavior and it presents the universal limits for the full rebound and adhesion. This work may deepen our understanding of the interaction mechanism between the droplet and cold surface in the impacting-freezing process and provides reference for the associated applications and technologies in anti-icing/frosting and self-cleaning. [Display omitted]